Expression of Nogo-A on the retina in rat model with chronic ocular hypertension - Nie, Qing-Zhu (International Journal of Ophthalmology Press, 2010)
AIM: To study the expressive variation of Nogo-A on rat retina in the process of chronic ocular hypertension. METHODS: Thirty-six healthy adult male Wistars were randomly divided into control group (6 rats) and chronic hypertension group (30 rats). Chronic hypertension was created by cauterizing the superficial scleral veins. Immunohistochemistry technique was used to evaluate the expressive varieties of Nogo-A at different time points during the course of chronic ocular hypertension. RESULTS: The success of the model was indicated by over 40% of increase in the IOP as compared with normal rats. Compared with control group, as time passed chronic hypertension group gradually had detectable morphology changes in the retina. At the 21st day of chronic ocular hypertension, retinas became thinner and the quantity of retinal ganglion cells (RGC) decreased (P<0.05). Assoicated with the morphological changes, the expression of Nogo-A was strongly increased (P<0.05). CONCLUSION: Myelin associated protein Nogo-A plays a part in the process of chronic ocular hypertension.